BENTUK PENYAJIAN TORTOR PADA GONDANG NAPOSO DI KECAMATAN PANGURURAN KABUPATEN SAMOSIR - Marta Sinaga (Gesture: Jurnal Seni Tari, 2016)
This study aims to determine how the form of presentationTortor in Gondang Naposo in District Pangururan Samosirregency. The theoretical foundation of this researchsubscribes to the theory that were examined, the theory ofpresenting the conceptual framework as a translation problemcontained therein.This research is a qualitative descriptivestudy. Data collected by field observations, with videocapture, documentation, and conduct interviews with sources,as well as complete the data through research in the area ofthe District Pangururan Samosir by making artists and localtraditional leaders as the population in the research.Theresults based on the data that has been collected can be seenthat Tortor in Gondang Naposo a means to buildrelationships of young generation and maturation spirit ofindependence and often the scene of the discovery of a matewho follow the customs of Batak Toba. Gondang naposoevent held for two days and started before parnakkok nimataniari (sunrise). The first day of the three materials areimplemented; martonggo raja (inviting parents to participatein the event), ulaon na hohom (only sound gondang) and oldmambuat ni gondang (hasuhutan invoke blessings on MulaJadi  Na  Bolon).  The  second  day  gondangnaposoimplementation. In Godang naposo tortor there are seventortor, namely; tortor mula-mula, tortor somba, tortormangaliat, tortor sibunga jambu, tortor hatasopisik, tortorsimonang-Monang, tortor hasahatan sitio-tio.